2013
DOI: 10.1148/radiol.13121598
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Hyperintensities: Use of Aortic Arch Pulse Wave Velocity to Predict Volume Independent of Other Cardiovascular Risk Factors

Abstract: Purpose:To evaluate the relationship between pulse wave velocity (PWV) from the aortic arch and subsequent cerebral microvascular disease independent of other baseline cardiovascular risk factors among the participants in the multiethnic Dallas Heart Study. Materials and Methods:Each subject gave written consent to participate in this HIPAA-compliant, institutional review board-approved prospective study. Aortic arch PWV was measured with phase-contrast magnetic resonance (MR) imaging in a population sample (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…Lastly, the FHS consists of predominantly white participants of Western European ancestry, potentially limiting the generalizability of our findings to people of other ethnicities. However, our results are consistent with studies incorporating other races and ethnicities, which have reported associations of arterial stiffness with future WMHV 28,29 and with cognitive impairment by Mini-Mental State Examination. 32 Future confirmation of our results in larger population samples and with longer follow-up is warranted.…”
Section: Methods Study Participants the Framingham Heartsupporting
confidence: 91%
See 1 more Smart Citation
“…Lastly, the FHS consists of predominantly white participants of Western European ancestry, potentially limiting the generalizability of our findings to people of other ethnicities. However, our results are consistent with studies incorporating other races and ethnicities, which have reported associations of arterial stiffness with future WMHV 28,29 and with cognitive impairment by Mini-Mental State Examination. 32 Future confirmation of our results in larger population samples and with longer follow-up is warranted.…”
Section: Methods Study Participants the Framingham Heartsupporting
confidence: 91%
“…In earlier cross-sectional analyses, baseline blood pressure and aortic PWV similarly predicted WMHV several years later in population-based cohorts. [28][29][30] In our sample, CFPWV was associated with WMHV, predominantly in participants aged 65 years or older, in cross-sectional analyses, 11 but was not associated with progression of WMHV. A possible explanation for this finding might be that our middle-aged cohort was relatively healthy and younger than other cohorts 10,28 in which associations between arterial stiffness and WMH have been observed.…”
Section: Methods Study Participants the Framingham Heartmentioning
confidence: 51%
“…Gray and white matter volumes were calculated as previously described (16), and lacunar infarcts and cerebral microbleeds were evaluated as previously reported (17). White matter lesion volume in millimeters was automatically quantified by using a previously validated method (18). In short, after initial tissue segmentation (18), white matter masks generated by FSL were spatially transformed to FLAIR images by using the FLIRT tool (19).…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…DHS-2 was conducted from September 2007 to December 2009. For more information about DHS-2 please see these references (King et al, 2013;Kozlitina and Garcia, 2012;Lucarelli et al, 2013).…”
Section: Participants and Assessmentsmentioning
confidence: 99%